Electric Polarity‐Dependent Modification of the Fe/BaTiO3 Interface. Issue 4 (16th December 2015) - Bisht, Manisha; Couet, Sebastien; Lazenka, Vera; Modarresi, Hiwa; Rüffer, Rudolf; Locquet, Jean‐Pierre; Van Bael, Margriet J.; Vantomme, André; Temst, Kristiaan
Abstract : The functionality and electronic properties of metal/ferroelectric systems rely heavily on the chemical and structural properties of the interface. The isotope sensitive technique of nuclear resonant scattering is used to selectively study the chemistry and magnetic state of the Fe/BaTiO3 interface. An electric polarity‐dependent modification of the metal/ferroelectric oxide interface has been systematically observed. The results show that the interface can be oxidized or reduced by inverting the polarity of the electric field applied across the interface above a threshold field value of ±400 kV m −1 . Remarkably, the final interface state depends on the polarization history of the system. Based on these results, a model for the electric field induced ion transport at the Fe/BaTiO3 interface has been suggested. Such subtle structural changes at the interface deteriorate the magnetoelectric coupling. However, for certain applications where an oxide layer is required at metal/ferroelectric oxide interfaces, the electric fields can be used to control interdiffusion processes. Abstract : Metal/ferroelectric interfaces are fundamental components in many devices. The functionality of such heterostructures is largely determined by the precise interface structure and composition. Understanding the effect of an electric field on the interface chemistry is crucial for realizing stable interfaces. It has been observed that electric field driven ion‐transport can occur across the interface. As a result, polarity‐dependent oxidation or reduction of the metal layer occurs.